Impact of Socioeconomic Factors on Life Expectancy in Pakistan - Khan, Ayub (International Journal of Modern Risk Management, 2023)
Purpose: The aim of the study was to examine the impact of socioeconomic factors on life expectancy in Pakistan Methodology: The study adopted a desktop methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library Findings: Socioeconomic factors have a significant impact on life expectancy in Pakistan. Higher education, greater access to healthcare, and higher income levels are associated with longer life expectancies. Gender disparities exist, with women generally having longer life expectancies than men due to differences in healthcare access and lifestyles. Urban areas tend to have higher life expectancies compared to rural areas due to better healthcare facilities and resources. These findings highlight the need for targeted policies and interventions to address disparities and improve overall population health in Pakistan. Unique Contribution to Theory, Practice and Policy: The socioeconomic development theory, the well-being theory & the social ecology theory may be used to anchor future studies on the examining impact of socioeconomic factors on life expectancy in Pakistan. Invest in the expansion and improvement of primary healthcare services, especially in rural and underserved areas. Develop policies that specifically aim to reduce health inequalities, such as initiatives to improve healthcare access in remote areas and interventions to address disparities in nutrition and sanitation.